Pioneering precision: unraveling cellular bioenergetics with ph-control - Ghaffari Zaki, Asal; Miri, Seyed Mohammad; Çimen, Şeyma; Akgül Çağlar, Tuba; Yiğit, Esra Nur; Aydın, Mehmet Şerif; Öztürk, Gürkan; Eroğlu, Emrah (My University, 2024)
[Abstract Not Available]
Keywords: Biochemistry; Molecular Biology; Endocrinology; Metabolism